THE EFFECT OF GIVING LAMTORO LEAF JUICE (Leucaena leucocephala) IN DRINKING WATER ON THE PERFORMANCE OF MALE BALINESE DUCKS - K. T. D., Deliana; Dewi, G. A. M. K.; Siti, N. W. (Jurnal Peternakan Tropika; Vol 12 No 2 (2024): Vol. 12 No. 2 Tahun 2024; March - April, 2024)
This study aims to determine the effect of giving lamtoro leaf juice in drinking water on the performance of male Bali ducks, which was carried out for 8 weeks. The design used was a completely randomized design (CRD) with 4 treatments, 4 replications, and each experimental unit used 3 male Bali ducks with homogeneous body weight. The treatment given to Bali ducks was various in the type of lamtoro leaf juice in drinking water, namely: P0 = male bali ducks given drinking water without lamtoro leaf juice, P1 = male bali ducks given 2% lamtoro leaf juice to drink, P2 = male bali ducks given drinking water of 4% lamtoro leaf juice, and P3 = male bali ducks given drinking water of 6% lamtoro leaf juice. The variables observed were: final body weight, weight gain, ration consumption, drinking water consumption, and feed convertion ratio (FCR) . The results of the study showed giving lamtoro leaf juice in drinking water by 2%, 4%, and 6% were not significantly different (P> 0.05) on final body weight, weight gain, ration consumption, drinking water consumption, FCR compared to treatment without leaf juice lamporo (P0). This study can be concluded that the administration of lamtoro leaf juice in drinking water as much as 2%, 4% and 6% has no effect on the performance of male Bali ducks.